(untitled) (SAARC Journal of Agriculture, 2025)
Mango mealybug (Drosicha mangiferae) is a cryptic, destructive and polyphagous pest in South Asia and its adjacent countries. It was a wide host range, and Jackfruit, Artocarpus heterophyllus is a most vulnerable host for this pest. Various mechanical barriers and chemical insecticide with mechanical blockade were tested and validated for managing D. mangiferae in Jackfruit orchard. Among physical barriers, double girdle alkathene bands with grease were found to be highly effective followed by the single alkathene band with grease, to restrict the upward movement of nymphs towards the plant canopy. Amid various chemical treatments with mechanical blockade, the combined application of single alkathene band with grease and spinosad suppressed the mealybug population by 87.41 per cent of 1st instar numphs followed by application of single alkathene band with grease and antario (81.21%). But the effectiveness of chemical pesticides comparatively decreases with the nymphal stages since 2nd and 3rd instar nymphs develop waxy coating which protect them from penetration of pesticide. The physical modules based upon alkathene band are recommended for the eco-friendly management of D. mangiferae on jackfruit plant and this technique has the potential to be adopted by resource-poor farmers in Bangladesh. SAARC J. Agric., 23(1): 82-93 (2025)